A work-based approach for improving students’ performance in the college general English class - Pan, Yi-Ching (Universitas Ahmad Dahlan, 2024)
Many university students in Taiwan have complained that the general English class is not very exciting nor useful for the workplace due to its exam-oriented and teacher-centered instruction focus. Such negative impressions often lead to a low motivation toward learning English and affect students’ learning outcomes. This study aimed to establish an innovative work-based teaching approach and to explore whether it can help enhance students’ motivation to learn English, positively impacting their overall performances. The work-based teaching approach included job-seeking activities involving self-introduction and resume writing, as well as product introduction tasks, fostering student participation, teacher-student interaction, and balanced summative-and-formative assessments. The study recruited 129 second-year university students in the general English class for an 18-week course where they were required to complete work-based tasks and assessments. A triangulation of research methods was employed to collect both qualitative and quantitative data from questionnaires, student formative and summative assessment, reflection journals, and student interviews. Three major findings arise from this study: 1) students’ score gain on TOEIC pre- and post-tests was statistically significant; 2) students offered positive views on the diverse, interactive, and communicative teaching methods that enhanced their understanding and application of workplace English; and 3) performance assessment played a more important role in increasing students’ learning interest and motivation than traditional paper-and-pencil tests. This study concludes with some pedagogical implications and suggestions for future research.